Ispol'zovanie cifrovych technologij, kak metodov issledovanija v trenirovocnom processe - Zarubina, M. S. (Uchenye zapiski universiteta imeni P.F. Lesgafta, 2019)
The modern training system in sport demands continuous monitoring and evaluations of the functional condition of the athlete for creation of individual approach to training process and its fast adjustment. Today there is huge number of the methods and ways of using the digital technologies in training of the athletes of various levels. The main problem of use of the digital technologies is connected with their introduction in training process. Not many clubs and teams are able to afford to use the digital technologies for monitoring of the condition of athletes. First, there is lack of informing on use of the digital technologies. Secondly, there is the insufficient number of the experts capable to provide methodical support for monitoring of the athletes. Thirdly, use of information technologies demands financial expenses that will be not always profitable. This article has analyzed the use of the digital technologies in the training process, as research methods in sports training.